(untitled) (Indonesian Journal of Science and Technology, 2025)
hemical kinetics is a fundamental field of study that focuses on the rates of chemical reactions and the factors influencing them. Determining the rate and order of the chemical reaction is an important aspect of understanding the reaction mechanism. This article presents a step-by-step guide to calculate and determine the rate and order of the reaction through a comprehensive analysis of experimental data. We discussed the concept of chemical kinetics, the integration of the kinetic order method, and the curve-fitting analysis technique. Several case studies are also included to provide practical applications of the theory outlined. This proposed guide aims to provide students, educators, researchers, and practitioners with a systematic approach to specify and verify prospective kinetic models, enabling them in decision-making, improving, and optimizing chemical reaction processes.